2020
DOI: 10.3233/jad-190825
|View full text |Cite
|
Sign up to set email alerts
|

Family History is Associated with Phenotype in Dementia with Lewy Bodies

Abstract: It is currently unknown whether patients with dementia with Lewy bodies (DLB) with relatives with dementia or Parkinson's disease (familial DLB patients) have a different phenotype than sporadic DLB patients. In this study, we aimed to examine disease onset, rate of cognitive decline, survival and Alzheimer's disease (AD) biomarkers in patients with dementia with Lewy bodies (DLB) with a family history of dementia or Parkinson's disease (familial DLB, n = 154) and sporadic DLB patients (n = 137), using linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…In agreement with our data, previous studies have reported a median survival in DLB ranging from 2 to 7 years [23,24]. Clinical subtypes did not appear to influence survival in our study, in contrast to the literature, where inaugural visual hallucinations were correlated with shorter survival and parkinsonism was rather associated with a longer survival [24][25][26][27]. Indeed, Jellinger et al showed that the presence of parkinsonism as the initial symptom in Lewy body dementia (LBD), which encompasses both DLB and Parkinson's disease with dementia (PDD), can have a significant impact on mortality and is associated with a longer survival rate.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with our data, previous studies have reported a median survival in DLB ranging from 2 to 7 years [23,24]. Clinical subtypes did not appear to influence survival in our study, in contrast to the literature, where inaugural visual hallucinations were correlated with shorter survival and parkinsonism was rather associated with a longer survival [24][25][26][27]. Indeed, Jellinger et al showed that the presence of parkinsonism as the initial symptom in Lewy body dementia (LBD), which encompasses both DLB and Parkinson's disease with dementia (PDD), can have a significant impact on mortality and is associated with a longer survival rate.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, the median survival of DLB our study was 6 years. In agreement with our data, previous studies have reported a median survival in DLB ranging from 2 to 7 years [23,24]. Clinical subtypes did not appear to influence survival in our study, in contrast to the literature, where inaugural visual hallucinations were correlated with shorter survival and parkinsonism was rather associated with a longer survival [24][25][26][27].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…2 A number of people affected by dementia have been increasing rapidly, and it is predicted that, for every 3 s, a new case of dementia has been reported worldwide. Various factors such as age, 3 family history, 4 and heredity 5 account for the development of AD. Among these, age is the greatest risk factor for AD as the prevalence of the disease increases with the increasing age.…”
Section: Introductionmentioning
confidence: 99%